PERCEPEREA ŞI REALIZAREA CALITĂŢII ÎN EDUCAŢIE - USM ADMIN (Moldova State University, 2007)
The article treats the most actual subjects of educational sciences nowadays - the role of teacher in obtaining quality in education. Today it should be developed the proficiency of actual and future teachers to make the curriculum for new school courses in accordance with the requirements of all beneficiary of the educational system. In this context it is neces- sary to know the requirements and implement the theoretical and practical module in refresher and university courses.